2011
DOI: 10.1002/cctc.201100225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co‐Components on the State of Pd and the Performance of Supported Pd/TiO2 Catalysts in the Gas‐Phase Acetoxylation of Toluene

Abstract: The effect of the co‐components Mn, Co, Au, and Sb with a wide range of standard reduction potentials (Mn2+/Mn: E°=−1.18 V; Co2+/Co: E°=−0.28 V; Sb3+/Sb: E°=+0.2 V; Au3+/Au: E°=+1.52 V) on the catalytic performance of 10 wt % Pd, 8 wt % M/TiO2 (M=Mn, Co, Sb, Au) catalysts in the gas‐phase acetoxylation of toluene to benzyl acetate has been studied. Co‐components with low E° are more active, but less selective than those with high E°. Co‐components with low E° (Mn, Co) stabilize Pd in its oxidized form, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 34 publications
11
13
0
Order By: Relevance
“…This has been explained by the formation of Pd surface oxides. XANES revealed that this oxidized Pd was not only present at the surface, as proposed previously,7 but even in the bulk of the particles. Apart from Pd surface oxide, another possible explanation of such slightly higher Pd binding energies around 335.5 eV, as found for Pd,Mn‐u11, was reported for a near‐surface Pd carbide investigated by in situ XPS 2628.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This has been explained by the formation of Pd surface oxides. XANES revealed that this oxidized Pd was not only present at the surface, as proposed previously,7 but even in the bulk of the particles. Apart from Pd surface oxide, another possible explanation of such slightly higher Pd binding energies around 335.5 eV, as found for Pd,Mn‐u11, was reported for a near‐surface Pd carbide investigated by in situ XPS 2628.…”
Section: Resultssupporting
confidence: 81%
“…[13] As ac onsequence,t he FTs( Figure4d)showed as hift of R to higher values compared to that of the Pd-foil reference (2.744 ). Thus, the first PdÀPd shell in the Pd,Mn-u11, Pd,Co-u11, and Pd,Sb-u11w as observed at R PdÀPd = 2.80, 2.79, and 2.76 , respectively.T hese values confirmedt he lattice expansion already seen for these materials by XRD [7] and pointed to the incorporation of othere lements into the Pd lattice.O nt he basis of TG investigations combined with XRD, we have previously proposed that carbon is preferentially incorporated into the Pd lattice when Mn or Co is present as co-component,a nd incorporation of Sb was anticipated for Pd,Sb-u11c atalysts. [7] In this former study,i tc ould be shownt hat regenerationa t3 00 8Ci na ir led to the typical Pd lattice parameters in the case of Mn and Co as co-components, which was explained by removal of carbon.…”
Section: Xas Studyatc O-componente Dgessupporting
confidence: 77%
See 2 more Smart Citations
“…6,7 Our group has intensively investigated acetoxylation of toluene over supported Pd-containing catalysts with the purpose of optimizing their composition 8,9 and reaction conditions. 3 The major drawback of such materials is their on-stream behavior, i.e.…”
Section: Introductionmentioning
confidence: 99%